EXAMINING THE IMPACT OF IMAGE AUGMENTATION ON OBJECT DETECTION AND CLASSIFICATION TO IMPROVE PERFORMANCE OF SITUATIONAL AWARENESS SYSTEMS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Situational Awareness (SA) and Artificial Intelligence (AI) go hand-in-hand in future applications, be that civilian applications, disaster relief or especially in the military domain. There, providing the most information, as quickly and as precisely as possible is crucial to completion of the given mission both in acquiring and denying the materiel and personnel. Object detection and classification are integral parts of this and will be the cornerstone in the coming years for developments and advances in civilian and military life. it is vital that these systems can operate in all weather conditions and be able to discern subtle differences in the observed objects, without relying on additional equipment.